2017
DOI: 10.1111/tpj.13573
|View full text |Cite
|
Sign up to set email alerts
|

MSH1 maintains organelle genome stability and genetically interacts with RECA and RECG in the moss Physcomitrella patens

Abstract: Chloroplast and mitochondrial DNA encodes genes that are essential for photosynthesis and respiration, respectively. Thus, loss of integrity of the genomic DNA of organelles leads to a decline in organelle function and alteration of organelle genetic information. RECA (RECA1 and RECA2) and RECG, which are homologs of bacterial homologous recombination repair (HRR) factors RecA and RecG, respectively, play an important role in the maintenance of integrity of the organelle genome by suppressing aberrant recombin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 33 publications
(65 reference statements)
2
49
0
Order By: Relevance
“…Sandhu et al (2007) showed that modulation of MSH1 expression by RNA interference results in heritable CMS in tobacco (Nicotiana tabacum) and tomato (Solanum lycopersicum) plants. Our results here showed that RECX OEX led to higher induction of recombination in mtDNA than occurred upon MSH1 mutation in P. patens (Odahara et al, 2017). RECX OEX, which should be easier than RNA interference, may be another way to induce CMS in angiosperms.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Sandhu et al (2007) showed that modulation of MSH1 expression by RNA interference results in heritable CMS in tobacco (Nicotiana tabacum) and tomato (Solanum lycopersicum) plants. Our results here showed that RECX OEX led to higher induction of recombination in mtDNA than occurred upon MSH1 mutation in P. patens (Odahara et al, 2017). RECX OEX, which should be easier than RNA interference, may be another way to induce CMS in angiosperms.…”
Section: Discussionmentioning
confidence: 63%
“…The eFP expression profiles of RECX and other genes involved in the maintenance of organelle genome stability revealed a positive relationship between their expression, except for RECA2. RECG, MSH1A, MSH1B, and RECX function in both chloroplasts and mitochondria (Odahara et al, 2015b(Odahara et al, , 2017, but their gene expression increased with the increasing expression of mitochondrial RECA1 rather than chloroplast RECA2. Given that the effects of RECG, MSH1B, or RECX KO were more prominent in mtDNA than in cpDNA (Odahara et al, 2015b(Odahara et al, , 2017, this stronger relationship with mitochondrial RECA1 Figure 6.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Instead, characterization of cytoplasmic genomes in these mutants has revealed structural 76 rearrangements resulting from ectopic recombination between small repeats (24,25,28). These 77 findings have led to the prevailing view that the primary role of MSH1 is in recombination 78 surveillance rather than in correction of mismatches or damaged bases (24,26,(29)(30)(31)(32), as is the 79 case for some other members of the mutS gene family (33).…”
mentioning
confidence: 99%
“…Nuclear genomes of P. patens and other plant species encode several homologs of bacterial HRR factors, although some homologs have not been identified in the genomes of P. patens and other plant species, on the basis of sequence similarity. [25] RecA is a key factor in HRR, as it binds to single-stranded DNA (ssDNA) and identifies homologous sequences to perform strand exchange between them [27]. Nuclear DNA of P. patens encodes two types of RecA homologs, RECA1 and RECA2, which show moderate sequence similarity.…”
Section: Plant Homologs Of Bacterial Proteins and Their Localizationmentioning
confidence: 99%